Identification of Key Residues Essential for the Activation of Plant Immunity by Subtilisin From Bacillus velezensis LJ02 - Hu, Jianan; Chang, Ruokui; Yuan, Yujin; Li, Zhuoran; Wang, Yuanhong (Frontiers in Microbiology, 2022)
Subtilisin, a serine protease, can trigger defense responses in a wide variety of plants, both locally and systemically, to protect against pathogens. However, key residues of subtilisin to improve resistance to plant diseases remain unknown. In this study, Nicotiana benthamiana (N. benthamiana) leaves expressing subtilisin from Bacillus velezensis LJ02 were shown to improve protection against Botrytis cinerea (B. cinerea). Furthermore, the underlying mechanism that LJ02 subtilisin improved the protective effect was explored, and the direct inhibitory effect of subtilisin on B. cinerea was excluded in vitro. Subsequently, reactive oxygen species (ROS) burst and upregulation of resistance-related genes in systemic leaves of N. benthamiana further verified that subtilisin could induce systemic protection against B. cinerea. G307A/T308A and S213A/L214A/G215A subtilisin significantly reduced the ability to resist B. cinerea infection in N. benthamiana. Furthermore, the ROS content and expression levels of resistance-related genes of both mutants were significantly decreased compared with that of wild-type subtilisin. This work identified key residues essential for the activation function of subtilisin plant immunity and was crucial in inducing plant defense responses against B. cinerea.